Effect Of Clay Upper Sand Soils On Skirted Footing Due To Vertical Loading - Halabia, Ali F A, Anto Budi Listyawan, S.T., M.Sc (2017)
The foundation is element of the building structure which connects the structure to the ground, and transfers loads from the structure to the ground. Skirts are used to improve the bearing capacity of shallow footings on clay upper sand soil by constraining the soil beneath and containing the plastic flow of soil. They are used as an alternative to deep foundations in soils with low strength at the surface, the bearing capacity formulation is used in the analysis of failure. The research are performing nine laboratory experiments on circular steel footings of different diameters footing made of steel diameter 75 mm, 100 mm and 150 mm with length of skirt 100 mm and 150 mm on clay upper sand by keeping the similar water content and compaction method, the research compared between clay upper sand and sand upper clay. From the result show the value of bearing capacity of clay upper sand greater then sand upper clay. The results from the laboratory show that the skirt is effectively to reduce the foundation settlement on clay which is observed on similar load 1 kN. The observations on L/D ratio on similar diameter show that the higher L/D ratio the smaller settlement. The load generally increase, when it is observed on settlement 3 mm with similar diameter, it shows that when increase the length of skirt increase the load value on the footing. This research include also comparing between the effect of skirted footing on clay upper sand and sand upper clay it is observed in same diameter footing and length of skirt smaller settlement and higher of loading for clay upper sand .